2021
DOI: 10.1111/php.13383
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Human Skin Models to KrCl Excimer Lamps: The Impact of Optical Filtering

Abstract: Far-UVC radiation is a promising technology that is potentially both effective at killing airborne microbes such as coronaviruses and influenza, and being minimally hazardous to the skin and eyes. Our previous studies on health risks from far-UVC have employed a krypton-chloride (KrCl) excimer lamp, emitting principally at 222 nm, supplemented with an optical filter to remove longer wavelength emissions inherent to these lamps. This study explores KrCl lamp health hazards by comparing filtered and unfiltered K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…This is proven further in a recent publication by Buonanno et al . ( 19 ). It is well recognized that it is important, when assessing the hazard from an ultraviolet source, to consider all wavelengths and plot the source spectrum on a logarithmic scale ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is proven further in a recent publication by Buonanno et al . ( 19 ). It is well recognized that it is important, when assessing the hazard from an ultraviolet source, to consider all wavelengths and plot the source spectrum on a logarithmic scale ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In further support of the computer modeling, Buonanno et al demonstrated that CPDs produced by a filtered KrCl excimer lamp were approximately 10–12% of the CPDs produced by an unfiltered source (8). MCRT simulation indicates that the Ushio Care222 (filtered) would produce 7% of the CPD produced by the source from Woods et al.…”
Section: Discussionmentioning
confidence: 95%
“…Buonanno et al. also demonstrated, in a skin model, limited DNA damage confined to the upper most layers of the skin only from a filtered KrCl lamp: 0.016% of keratinocytes had CPD at TLV which was 730 times less CPD than exposure to 254nm at TLV (8). In contrast, Shih et al showed prolific CPD throughout the epidermis from simulated sunlight exposure at just 80% of the Minimal Erythema Dose (MED) (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations